The Philosophical Method of Aristotle and Thomas in Contract Law Analysis - Abdorreza Alizadeh (روش شناسی علوم انسانی, 2019)
This article addresses the role of Aristotelian thought and method in contract analysis, and how this analytical method has transferred to modern thought through Christian theologians, especially Thomas Aquinas and late scholastics. The purpose of this research is to raise this significant legal challenge for Iranian law and to address the experiences of Western law in this problem. The result of this research is that, contrary to the appearance of Western philosophy that shows the foundations of Aristotelian thought have been severely criticized and discarded since the seventeenth century, the framework of the teachings of contract law has been based on Aristotelian and Thomasian thought, and more so by late scholastics and the Spanish natural law school and in fact, intellectuals like Hugo Grossius have finalized these preliminary intellectual works. Meanwhile, the influence of Iranian and Islamic philosophy and thought in these teachings, through their influence on St. Thomas, is not deniable. I hope that the study of this article will make Iranian law faculties more aware of their difficult and significant task ahead, and that cultural and scientific policymakers will know that the law school is not a place just for the production of legal degrees for individuals and that its work is more significant than the work of medical school.